Réponses

Meilleure réponse !
2013-06-18T19:05:55+02:00

a) 3x+4=2x+7

     3x-2x=7-4

     x=3

 

b) 2x-5=5x+1

     2x-5x=1+5

     -3x=6

      x= 6/-3

      x=-2 

  • Utilisateur Brainly
2013-06-18T21:45:15+02:00

Résoudre les équations suivantes :

a)

b) 

 

réponse:

a) 3x+4=2x+7

donc 3x-2x=7-4

donc x=3

 

b) 2x-5=5x+1

donc 2x-5x=1+5

donc -3x=6

donc x=6/(-3)

donc x=-2

 

complément de COURS :

ax+b=cx+d

donc ax-cx=d-b

donc (a-c)x=d-b

donc x=(d-b)/(a-c) si a est différent de c